Construction and Activity of a New Catalytic System in the Hydrolysis of Bis(4‐nitrophenyl) Phosphate Ester. Issue 6 (23rd April 2013) - Xie, Jiaqing; Li, Ci; Wang, Min; Jiang, Bingying
ABSTRACT A new catalytic system containing an unsaturated heterocyclic nitrogen ligand and lanthanum(III) was constructed and used as a catalyst in the hydrolysis of bis(4‐nitrophenyl) phosphate ester (BNPP) in this work. The results indicated that this catalytic system showed greater catalytic activity in the hydrolysis of BNPP and better reproducibility and stability than other similar lanthanum(III) systems. The catalytic rate of the BNPP hydrolysis was about 107‐fold faster than that of its spontaneous hydrolysis at the same conditions. Compared with the previous Cu(II) or Ni(II) complex containing the same ligand in the water, the activity of the macrocyclic La(III) complex increases ca. 103‐fold for BNPP catalytic hydrolysis. The experimental data showed that the monohydroxy complex made of the heterocyclic nitrogen ligand and lanthanum(III) is the real active species as a catalyst in BNPP catalytic hydrolysis.